Time Pressure and Regret in Sequential Search - Felix Klimm; Martin G. Kocher; Timm Optiz; Simeon Andreas Dermot Schudy (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Perceived urgency and regret are common in many sequential search processes; for example, sellers often pressure buyers in search of the best offer, both time-wise and in terms of potential regret of forgoing unique purchasing opportunities. Theoretically, these strategies result in anticipated and experienced regret, which systematically affect search behavior and thereby distort optimal search. In addition, urgency may alter decision-making processes and thereby the salience of regret. To understand the empirical relevance of these aspects, we study the causal effects of regret, urgency, and their interaction on search behavior in a pre-registered, theory-based, and well-powered experiment. We find that urgency reduces decision times and perceived decision quality but does not alter search length. Only very inexperienced decision-makers buy earlier when pressured. Anticipated regret does not affect search length (neither with nor without time pressure), while experienced regret leads to systematic adjustments in search length. Thus, we recommend that consumer protection policies should particularly focus on markets with inexperienced first-time buyers.
Keywords: C91; D01; D03; D18; D83; 330; sequential search; time pressure; regret; anticipated regret; experienced regret